Defining the transcriptional routes controlling lncRNA NEAT1 expression: implications in cellular stress response, inflammation, and differentiation - Sara De Domenico; Veronica La Banca; Silvia D’Amico; Sara Nicolai; Angelo Peschiaroli (Discover Oncology)
Abstract NEAT1 (Nuclear Enriched Abundant Transcript 1) is a long non-coding RNA playing a critical role in both physiological and pathological settings by directly modulating a variety of biological events, including transcriptional regulation, RNA processing, and chromatin remodeling. Multiple evidence demonstrated that different transcription factors and signaling pathways modulate biological processes by tightly regulating NEAT1 expression. These regulatory mechanisms act at different levels, allowing cells to rapidly modulate NEAT1 expression and dynamically respond to sudden changes in cellular conditions. In this review, we summarize and discuss the transcriptional routes controlling NEAT1 expression, emphasizing recent evidence showing the pivotal role of NEAT1 in regulating important biological processes, such as cellular stress response, inflammation, and cell differentiation.